Research Progress on Starch-Polyphenol Composite Film: from Functional Properties to Food Packaging Application - WANG Zhijing, CHEN Qianqian, CAI Jie (Shipin Kexue, 2024)
Plastic packaging pollution is a global environmental problem. Hence, the development of biodegradable materials has gained extensive attention in the field of food packaging. Starch, a common polysaccharide in nature, has the advantages of low price, safety, non-toxicity, and easy processing, and has shown great potential in the development of environmentally friendly food packaging materials. However, pure starch films have poor barrier performance and monotonous functional characteristics, which cannot satisfy people’s increasing requirements for food storage period and freshness. Polyphenols are natural antioxidants with a variety of beneficial health effects, so different types of polyphenols can be introduced into starch-based films to fabricate starch-polyphenol composite films with various functional properties. In this article, three preparation methods for starch-polyphenol composite films, extrusion, electrospinning and solvent casting are reviewed in terms of the preparation process, influential factors, advantages and disadvantages, and the interaction between starch and polyphenols is elucidated. The effects of adding polyphenols on physicochemical properties of starch-based composite films and their applications in the field of food packaging are analyzed, and future developments and challenges for starch-polyphenol composite films are discussed.